Updated Meta-analysis of Minimally Invasive Versus Open Surgery for Pancreatic Neuroendocrine Neoplasms. Issue 3 (March 2021) - Zhang, Wei; Zhang, Jianwei; Che, Xu
Abstract : Objectives: The aim of this study was to compare the short-term and long-term outcomes of minimally invasive surgery (MIS) with those of open pancreas surgery (OPS) for the treatment of pancreatic neuroendocrine neoplasms (pNENs). Methods: Studies reporting the effects of MIS and OPS for pNENs, published on PubMed, Embase, and Cochrane Library before May 2020 were reviewed. Results: Seventeen cohort studies with a total of 1853 patients were eligible for analysis, including 655 patients in the MIS group and 1198 patients in the OPS group. The estimated blood loss, postoperative hospitalization time, overall complications, severe complications, spleen preservation, mortality, and recurrence in the MIS group were lower than those in the OPS group. The R0 rate, 3-year overall survival (OS), and 5-year OS in the MIS group were higher than those in the OPS group. There were no significant differences in operative time, postoperative pancreatic fistula, clinical postoperative pancreatic fistula, postoperative bleeding, reoperation, readmission, and 1-year OS. Conclusions: Minimally invasive surgery can reach lower recurrence rate, higher long-term survival rate, and better outcomes in terms of estimated blood loss, postoperative hospitalization time, R0 rate, mortality, overall complications, and severe complications for pNENs. More high quality studies need to be conducted for further verification. Abstract : Supplemental digital content is available in the text.